Dirk Pitt : The Devil's Sea - Book 26 - Cussler, Dirk; Cussler, Clive (New York : G.P. Putnams Sons, 2021)
"Fearless adventurer Dirk Pitt must unravel a historical mystery of epic importance in [this] novel in the ... New York Times bestselling series created by the grand master of adventure Clive Cussler"--
Keywords: Pitt, Dirk -- (Fictitious character) -- Fiction; Aircraft accidents -- Fiction; Antiquities -- Fiction; Philippines -- Fiction; Tibet Autonomous Region (China) -- Fiction; Himalaya Mountains -- Fiction; Action and adventure fiction; Thrillers (Fiction)